Adults Newly Exposed to "Know the Signs" Campaign Report Greater Gains in Confidence to Intervene with Those Who Might Be at Risk for Suicide Than Those Unexposed to the Campaign - Ramchand, Rajeev (RAND Corporation, 2015)
Presents results of a one-year follow-up to a survey on Know the Signs, a California mass media suicide prevention campaign, and examines the effect of campaign exposure on respondents' confidence to intervene with someone at risk for suicide.